2014
DOI: 10.1080/01490451.2013.879508
|View full text |Cite
|
Sign up to set email alerts
|

Sulphate-controlled Diversity of Subterranean Microbial Communities over Depth in Deep Groundwater with Opposing Gradients of Sulphate and Methane

Abstract: The groundwater system in Olkiluoto, Finland, is stratified with a mixing layer at a depth of approximately 300 m between sulphaterich, methane-poor and sulphate-poor, methane-rich groundwaters. New sequence library data obtained by 454 pyrotag sequencing of the v4v6 16S rDNA region indicated that sulphate-reducing bacteria (SRB) dominated the mixing layer while SRB could not be detected in the deep sulphate-poor groundwater samples. With the indispensable support of the sequence data, it could be demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 33 publications
3
38
1
1
Order By: Relevance
“…The Shannon–Weaver index and the Simpson index were estimated to compare species diversity between the underground boreholes at the Mizunami URL and the GTS (http://onlinelibrary.wiley.com/doi/10.1111/1758-2229.12379/suppinfo). Despite the difference in species richness, the two indices were relatively similar and comparable with those estimated for the previously investigated underground borehole at the Scandinavian Shield (Pedersen et al ., ). The species diversity was slightly higher at 09MI21‐2 than at 09MI21‐4, probably because of the high proportion of a Nitrospirae OTU (Granitic URL_1) at 09MI21‐4.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The Shannon–Weaver index and the Simpson index were estimated to compare species diversity between the underground boreholes at the Mizunami URL and the GTS (http://onlinelibrary.wiley.com/doi/10.1111/1758-2229.12379/suppinfo). Despite the difference in species richness, the two indices were relatively similar and comparable with those estimated for the previously investigated underground borehole at the Scandinavian Shield (Pedersen et al ., ). The species diversity was slightly higher at 09MI21‐2 than at 09MI21‐4, probably because of the high proportion of a Nitrospirae OTU (Granitic URL_1) at 09MI21‐4.…”
Section: Resultsmentioning
confidence: 97%
“…As for the terrestrial basement, underground facilities are frequently used for microbiological investigations, because short-range drilling from the underground can significantly reduce contamination in comparison with long-range drilling from the land surface. Underground facilities constructed in the granitic basements of Canadian and Scandinavian Shields have been microbiologically investigated (Jain et al, 1997;Pedersen, 2000;Pedersen et al, 2014). During the construction of underground facilities, the intrusion of shallow groundwater into the deep aquifer is extensive and significantly alters the chemistry and microbiology of the original groundwater (Banwart et al, 1996;Gascoyne and Thomas, 1997;Pedersen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow cells were loaded with garnet grains and glass beads as solid support for biofilm growth. These surfaces were chosen as (i) they were sterile, DNA-free, and RNAse/DNAse-free and could be sterilized by heating to 450 °C, respectively; (ii) in testing biofilm formation at the Äspö HRL, it was found that bedrock from the same environment was porous and that unattached minerals and particles disrupted DNA extractions from the formed biofilms [13, 14, 32]; and (iii) the fracture surfaces in the bedrock are mineralogically very heterogeneous consisting of various proportions of primary minerals (e.g., quartz, feldspar, plagioclase, and mica) and secondary precipitates (e.g., calcite, pyrite, epidote, Fe-oxides, and clay minerals) [33, 34]. Therefore, the flow cell system was simplified by using a single silicate mineral (garnet) that in terms of biofilm formation can be considered as representative for the silicate rocks (granites) in the Äspö HRL.…”
Section: Resultsmentioning
confidence: 99%
“…There was extremely high Desulfobulbaceae abundance in the upstream region of the second confined groundwater body corresponding to the high concentration of SO 4 2− . Previous reports indicated that the presence of SO 4 2− in groundwater significantly influenced the diversity of subterranean microbial communities (Pedersen, Bengtsson, Edlund, & Eriksson, ). Particularly, several sulphate‐reducing bacteria had strong negative interactions with other microorganisms (Deng et al, ).…”
Section: Discussionmentioning
confidence: 99%